History's flagstones: Nuruddin Farah and Italian postcolonial literature - Fotheringham, Christopher (My University, 2016)
This study presents an argument for considering the works of Nuruddin Farah translated into Italian as core texts in the body of postcolonial Italian literature. The study focusses on Farah’s first two trilogies: Variations on the Theme of an African Dictatorship and Blood in the Sun. It is shown in this study that the translated versions of the novels making up these two trilogies, the former in particular, provide rare and unique narrative content capable of directly challenging the myths and misconceptions that have come to characterise the memory of the Italian colonial period. These works are read contrapuntally against historical narrative tropes that were used to represent Africa and Africans in Italian colonial literature. Farah’s work is also compared with the writing of contemporary writers of African descent whose work is at the forefront of interest in postcolonial studies in Italy. This study shows how Farah’s work complements and enhances this emerging literary tradition. It is then shown that, despite this obvious potential, the status of Farah’s work in the Italian literary system has been limited by an unwelcoming publishing climate for African literature in Italy. The study then provides an analysis of the translations themselves focussing on three texts: Maps, Gifts and Sweet and Sour Milk. This analysis takes the form of a descriptive comparative analysis aimed at establishing the extent to which the three different Italian translators of these texts handled the translation of stylistic features of the texts which signal their postcoloniality and their heritage of Somali oral poetry. It is concluded that, in the main, the translations are somewhat domesticated which has certain negative consequences in terms of their ability as texts to speak on behalf of the colonized people they represent. It is however noted that one text exhibits a greater tendency towards foreignization. By no means coincidentally, this text was produced by a translator with theoretical and practical experience in the field of postcolonial literature. The study concludes by conceiving of the trajectory of Nuruddin Farah’s work through the Italian literary system as a narrative of violence, resistance and retribution on either side of the colonial divide.
Thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Translation Studies at the University of the Witwatersrand, Johannesburg. 2015
Keywords: Farah, Nuruddin,|d1945--Criticism and interpretation; Postcolonialism in literature; Italian literature--History and criticism; Somalia--In literature